Latest Research into Quality Control - Akyar, Isin (IntechOpen, 2012)
Quality control has an emerging importance in every field of life. Quality control is a process that is used to guarantee a certain level of quality in a product or service. It might include whatever actions a business deems necessary to provide for the control and verification of certain characteristics of a product or service. With the improvement of technology everyday we meet new and complicated devices and methods in different fields. Quality control should be performed in all of those new techniques. In this book "Latest Research Into Quality Control" our aim was to collect information about quality control in many different fields. The aim of this book is to share useful and practical knowledge about quality control in several fields with the people who want to improve their knowledge.